Technical challenges of lymphadenectomy in renal carcinoma performed with a 3D laparoscopic approach at a low pressure pneumoperitoneum due to associated pulmonary pathology – case report - Bujoreanu, Cristina E.; Dor, Yarden; Petrut, Bogdan (Medicine and Pharmacy Reports, 2022)
We report the case of a 63-year-old male patient presenting left renal cell carcinoma (75/70/60 mm) associated with retroperitoneal lymph node masses (peri hilar of 15 mm; lombo-aortic of 50/40/30 mm), known also with chronic obstructive pulmonary disease GOLD4, sleep apnea and asthma with oxygen-dependent chronic obstructive respiratory insufficiency, a BMI of 37 with grade III obesity. Surgical treatment was performed using a 3D transperitoneal laparoscopic approach. The surgery lasted 131 minutes, with 400 ml blood loss and grade 1 Clavien-Dindo post operative complications. An optimal pulmonary ventilation of the patient during surgery required a low intra-abdominal pressure (10 mmHg) which raised technical difficulties due to the lymph node mass dissection from the great vessels in a small operative field on an already obese patient with a voluminous renal tumor. The 3D transperitoneal laparoscopic approach was feasible within safe oncologic parameters